PERFORMANCE ANALYSIS OF PDAM CLEAN WATER SERVICE NEEDS FOR DOMESTIC CUSTOMERS OF WAGINOPO VILLAGE, WANGI-WANGI DISTRICT, WAKATOBI DISTRICT - Jamiludin, Jamiludin; Wulandari, Esti; Tjendani, Hanie Teki (Transpublika Publisher, 2024)
Clean water is essential for society's basic needs like drinking, bathing, cooking, washing, and industrial purposes. Having clean water available in a community is crucial due to the busy nature of society. However, in Waginopo Village, the drinking water supply system is not functioning well. Reports show that the water from PDAM only runs every 2 days, once a week, and for a maximum of 12 hours. The aim of this research is to analyze the performance of PDAM Wakatobi's clean water services to meet the needs of the Waginopo Village community for clean water. In this research, not only numerical data will be collected, but also information about what the community desires regarding the performance of the clean water distribution system, so this research study approach uses a combination of quantitative and qualitative approaches. From the results of the analysis, it can be said that the performance of the Wakatobi Regency PDAM service for the Waginopo Village service area is based on the 6th assessment aspect, where the distribution aspect is assessed with a performance value of